Are UN Innovation Labs effective innovation models to meet the needs of communities in the humanitarian sector - Case Study Kosovo - DARKWA, IMMANUEL (Trinity College Dublin. School of Natural Sciences. Discipline of Geography, 2020)
Humanitarian action involves the provision of goods and services such as food, water, sanitation, disasters medical care, shelter and protection, during and soon after natural and human-made disasters (Sphere, 2004, p. 6). Diverse and often complex causes create situations that make the inhabiting of affected locations challenging. In a 2019 UNHCR report, global forced displacement increased again in 2018 to ca. 70.8 million individuals forcibly displaced worldwide, as a result of persecution, conflict, generalized violence, or human rights violations. In addition to providing humanitarian assistance to such populations in crisis, humanitarianism also deals with partnering with other stakeholders, interconnected entities - a "humanitarian system". Whilst lead responsibility in humanitarian responses lie with the affected State, international UN aid agencies assist by rallying the collective support of States to address the needs of affected communities. However, researchers have found that responses can be inefficient, can sometimes lead to dependency and are often unsustainable. With increasing numbers of displaced persons and related challenges facing aid organisations, researchers have argued that Innovation is now imperative in the humanitarian space. Humanitarian innovation is a means of invention, adaptation and improvement through finding and scaling solutions to problems, in the form of products, processes or service models, facing effective humanitarian assistance. Consequently, UN agencies are introducing mechanisms that seek to address needs through new practices. A preferred mechanism is a Lab model (Bloom and Faulkner, 2015). They have however queried the general understanding of innovation and what Lab mechanisms are truly achieving. Obrecht and Wagner (2016) also suggest that progress of measuring impact, as well as factors that contribute to successful innovations are unclear. Ramalingam, Rush et al. (2015) also note problems associated with fragmentation, coordination of innovation, actor and roles and the need to strengthen skills capacities and enablers of innovation etc. Thus, this research sought to establish whether UN Innovation Labs are effective innovation models to meet the needs of communities in the humanitarian sector? Following on from a preliminary key informant phase, the main data collection comprised 65 semi-structured interviews, 50 surveys and 2 focus group discussions. This study investigated Kosovo's UNICEF Innovations Lab, through a case study methodology, underpinned by constructivist principles, to elucidate what innovation outcomes are achieved through Lab mechanisms. It sought to identify how innovation is achieved by outlining project level features of Lab processes. It interrogated the model employed in light of the Living Lab model of open innovation and innovation ecosystems, identifying thereby key actors and their roles. To answer the main research question, it relied on contingency theory to identify dimensions of effectiveness. It then transposed its findings into contingency factors for effective Lab mechanisms within the context. The study revealed that an inclusive Living Lab model operating a multi - method approach, in a real life environment, with multi stakeholder participation, openness and active user involvement, a congruence of structure and context variables, leadership with distinctive attributes, made the examined open innovation model effective in achieving its goals and objective in the form of programme, product, service and process innovations within the context. The results of this study may be applied as guidelines for similar initiatives in humanitarian settings. However, there is need for further study to be conducted and recommends a multi case study approach to determine whether the model is the effective UN Innovations model to allow innovation to occur and to meet the needs of demographics in entirely humanitarian settings.
APPROVED
Keywords: Humanitarian action; Innovation Labs; Living Labs; Contingency Theory; Innovation; Innovation management and ecosystem; Humanitarian Innovation